2016
DOI: 10.1007/s00436-016-5175-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of arthropod-borne pathogens in sheep keds (Melophagus ovinus), Central Europe

Abstract: In the study, we screened a total of 399 adult sheep keds (Melophagus ovinus) for the presence of RNA and DNA specific for arboviral, bacterial, and protozoan vector-borne pathogens. All investigated keds were negative for flaviviruses, phleboviruses, bunyaviruses, Borrelia burgdorferi, Rickettsia spp., Anaplasma phagocytophilum, "Candidatus Neoehrlichia mikurensis," and Babesia spp. All ked pools were positive for Bartonella DNA. The sequencing of the amplified fragments of the gltA and 16S-23S rRNA demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
0
25
0
2
Order By: Relevance
“…However, two studies reported a failure to detect Rickettsia spp . in M. ovinus collected in Ethiopia and the Czech Republic [ 18 , 47 ]. Using next-generation sequencing, we similarly were unable to detect Rickettsia in two groups of M. ovinus collected from Jiuquan in Gansu Province, China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two studies reported a failure to detect Rickettsia spp . in M. ovinus collected in Ethiopia and the Czech Republic [ 18 , 47 ]. Using next-generation sequencing, we similarly were unable to detect Rickettsia in two groups of M. ovinus collected from Jiuquan in Gansu Province, China.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nelder et al [ 17 ] screened a 150 M. ovinus individuals for Coxiella burnetii , with negative results. Rudolf et al [ 18 ] also failed to find evidence of flaviviruses, phleboviruses, bunyaviruses, Borrelia burgdorferi , Rickettsia spp., Anaplasma phagocytophilum or Babesia spp. in M. ovinus .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two reports have shown the absence of Rickettsia spp. in M. ovinus collected in Ethiopia and the Czech Republic [13, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Assessing the microbial community of insect vectors could facilitate further studies with respect to how the microbiota interacts with vectors of animal parasites, as well as how to develop tools for biological control. There have been studies on the characteristics of microbial populations in the midgut of the male and female M. ovinus (Duan et al ., ), including comprehensive investigations of arboviral, bacterial and protozoan vector‐borne pathogens within M. ovinus (Rudolf et al ., ), as well as the characteristics of symbiotic systems associated with M. ovinus (Nováková et al ., ). However, the bacterial community in insects is not always stable.…”
Section: Introductionmentioning
confidence: 99%